Abram-se as cortinas : a história da formação teatral em Aracaju, Sergipe (1960-2000) - Benevides, Lourdisnete Silva (2015)
This research investigates the theatrical training in the City of Aracaju, between the 1960s and early 2000s, our empirical field, when there was not yet formal theatrical training school in their daily lives. In that theatrical context, which precedes the installation of the Bachelor s Degree in Theater/UFS, in 2007, the concern was to find out how was the formation of these Sergipe theatrical subjects and what were their artistic practices. We believe that they occurred from their informal trainings, rather than formal, and, for that we appropriated the studies of Maria da Glória Gohn s on non-formal education. We sought also examine and describe how the relations processes occurred, which they had with their theatrical learnings, taking into account the assessment of the relationship with the knowledge widely publicized by Bernard Charlot. Besides them, we are approaching the theoretical contribution of István Mésáros s, to remember the dinamics of learning as a constant in our lives; L. S. Vigotski, once considering the historical and social processes and Muniz Sodré, with his idea of an ecology of the knowledges, a pedagogy which houses diversity. The thesis considered the 49 semi-structured interviews with Sergipe theatrical artists and is based in the methodology of qualitative approach to oral history, understood by Carlos Sebe Bom Meihy as a way of doing and thinking oral research. However, the analysis met the few existing documents, when it was needed. By the way, in conjunction with the instruments of collecting field data, we performed a literature review focused in the context of theatrical training, mainly on the Sergipe theatrical training. We believe that the presentation of the results of this research, in fulfillment of the objectives of PPGED/UFS, line of research Educators Training: Knowledges and Skills, can help to foster new researches on the subject of Sergipe theater and its artistic doings.